2019
DOI: 10.4081/ripppo.2019.379
|View full text |Cite
|
Sign up to set email alerts
|

Reductions in transdiagnostic factors as the potential mechanisms of change in treatment outcomes in the Unified Protocol: a randomized clinical trial

Abstract: Transdiagnostic approaches emphasize on the share underlying features of emotional disorders. In their view, these transdiagnostic factors play an important role in the etiology, maintenance, and treatment of emotional disorders. This study aimed to investigate the transdiagnostic factors as the potential mechanisms of change in the Unified Protocol (UP) for the transdiagnostic treatment of emotional disorders outcomes. The present study is a randomized clinical trial. Twenty-six individuals were selected base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 48 publications
1
9
0
2
Order By: Relevance
“…On the other hand, emotion dysregulation defined as “maladaptive emotional responsiveness reflected in dysfunctional understanding, reactivity, and management” ( Mennin et al, 2007 ). Emotion regulation difficulties have been reported across a wide range of emotional problems ( Berking and Wupperman, 2012 ; Naragon-Gainey et al, 2017 ; Khakpoor et al, 2019 ). Steel (2007a) considers procrastination as a kind of dysfunctional, emotional driven self-regulation.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, emotion dysregulation defined as “maladaptive emotional responsiveness reflected in dysfunctional understanding, reactivity, and management” ( Mennin et al, 2007 ). Emotion regulation difficulties have been reported across a wide range of emotional problems ( Berking and Wupperman, 2012 ; Naragon-Gainey et al, 2017 ; Khakpoor et al, 2019 ). Steel (2007a) considers procrastination as a kind of dysfunctional, emotional driven self-regulation.…”
Section: Introductionmentioning
confidence: 99%
“…The triple vulnerability model and previous research have shown that UPs can effectively treat a range of emotional disorders based on providing flexibility and convenience (Ehrenreich-May et al ., 2017 ; Ehrenreich et al ., 2009 ; Farchione et al ., 2012 ; Kennedy et al ., 2019 ; Leonardo, Aristide, & Michela, 2021 ; O’donnell et al ., 2021 ; Sakiris & Berle, 2019 ; Steele et al ., 2018 ). Previously, the studies on the effectiveness of the UP on transdiagnostic factors have yielded promising results in adolescents and adults (Khakpoor, Bytamar, & Saed, 2019 ). In the present study, we aimed to evaluate UP effectiveness specifically in the paediatric population, by selecting three key transdiagnostic constructs (NA, AS, PC).…”
Section: Discussionmentioning
confidence: 99%
“…Given the association found between adolescent cannabis use and the severity of concurrent psychopathology, such as suicidal behavior (Gobbi et al, 2019), further development of prevention programs is needed. Subgroups of the most vulnerable adolescents could be identified using markers of increased cannabis use identified here, namely, hopelessness, rumination, or anomalous perception of reality (Khakpoor et al, 2019). These programs may incorporate individualized interventions focused on learning emotional management and regulation skills.…”
Section: Discussionmentioning
confidence: 99%
“…These variables increase the vulnerability to mental disorder and are factors in their maintenance. Early intervention of these variables can play a fundamental role in preventing and treating psychopathology (Khakpoor et al, 2019). Further, intervention of trandiagnostic variables could be a method of reducing risk of cannabis dependence.…”
Section: Introductionmentioning
confidence: 99%